Ketatanegaraan Klasik Hukum Adat Tengger Ditinjau dari Perspektif Politik Hukum sebagai Produk Budaya - Yanels Garsione Damanik; Fazal Akmal Musyarri; Muhammad Akbar Nursasmita; Elsa Assari; Dea Candori (CV Rewang Rencang, 2020)
This research takes the object of customary law that grows, develops and is adhered to by the Tengger Indigenous Law Society. The viewpoint taken in understanding the evolving law in the Tengger Indigenous Law Society as law is not written in the legal context as a product of culture. Law is essentially a form of cultural expression of society that radiates from the results of the copyright, taste and work of the community. So that the law basically has characteristics that are social and localistic. Although no more strict than written law equipped with a definite sanctions mechanism, but customary law managed to make the community run by following the social order as expected by the legislator, which allows the author to explore the legal value of Tengger's local constitutional law.